Feminism, Intersectionality, and Gender Category: Essential Contributions for Historical Thinking Development - Díez-Bedmar, María del Consuelo (Frontiers in Education, 2022)
The following article inquires in how introducing the gender category, feminism theories and intersectionality on Social Sciences Education, especially regarding to a historical thinking development, could be a key for the construction of a more critical and egalitarian future. The main research problem is to know how the use of the gender category is included, or not, on the development of historical thinking in the preservice teacher beliefs and how it could condition them when they work on historical and social problems in the classroom. The main objective is to analyze the historical thinking development on pre-service Spanish teacher students’ and their capacity for constructing critical discourses with a gender perspective. Pre-service teachers of five Spanish Universities (of the Primary and Secondary Education Degree) were inquired about a report from a digital newspaper version that force them to use historical thinking and to consider gender stereotypes and prejudices. Their responses were analyzed both qualitatively and quantitatively. The results indicate that pre-service teacher are not able to identify their own gender roles and prejudiced attitudes when they attempt to explain a social problem situation and they propose solutions, even when they could verify that there was another manner to understand this report. Hence, this research highlights the relevance of implementing the feminism, intersectionality and gender category for the historical thinking development since these future teachers need to work around democratic culture competences. By contrast, not to include this perspective leads to they will still maintain a historical thinking and democracy configured on hegemonic, heteropatriarchal, sexist and eurocentric cultural models.